The Effect of Debt-to-Equity Ratio, Return on Asset, Current Ratio, and Total Asset Turnover on Stock Price: The Intervening Effect of Intrinsic Value in Indonesia’s Retail Business - Andini Nurwulandari; Ririan Safiadi Wahid (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study examines the effect of Debt-to-Equity Ratio (DER), return on assets (ROA), current ratio (CR), and total asset turnover (TATO) on stock prices with their Intrinsic Value as intervening variables in retail companies in Indonesia. Data regarding retail companies were obtained from the Indonesia Stock Exchange, and secondary data on these companies' financial ratios were collected from Stockbit. Stock price data were sourced from Yahoo Finance, and the intrinsic value of shares was determined using the price-to-earning ratio method. Drawing on structural equation modeling, the findings demonstrate that DER and ROA exert a positive and statistically significant effect on intrinsic value. TATO, on the other hand, exhibits a negative and statistically significant effect on intrinsic value, while CR demonstrates a negative and non-significant effect. Regarding stock prices, DER and CR have a negative and statistically significant effect, while ROA and Intrinsic Value have a positive and statistically significant effect. TATO, however, shows a negative and non-significant effect on stock prices. Furthermore, DER has a positive and non-significant effect on stock prices through intrinsic value, whereas ROA has a positive and statistically significant effect on stock prices through intrinsic value. CR, on the other hand, exhibits a negative and non-significant effect on stock prices through intrinsic value, and TATO demonstrates a negative and statistically significant effect on stock prices through intrinsic value.